Social Marketing Strategy of Youthfel Indonesia in Effort to Realize the Right to a Good and Healthy Environment in Yogyakarta in 2023-2024 - Daffa Rakha Attalah; Taufiqur Rahman (Jogjakarta Communication Conference (JCC), 2025)
Feminism in popular culture has developed significantly, especially in the representation of women in the entertainment industry. Third-wave Feminism or post-feminism presents an image of women who are free, independent and empowered, but still attached to the values ​​of femininity constructed by the media. As one of the world's musicians who raised the theme of women's empowerment, Katy Perry successfully brought the concept of post-feminism by presenting the image of modern women through her music. Therefore, this research aims to find out the image of women constructed by Katy Perry through the song lyrics and video clip Woman's World. The research was conducted using Roland Barthes' semiotic method to reveal the signs of post-feminism in the song lyrics and video clip. The results found that Katy Perry's performance is in line with the concept of post-feminism which shows women as a figure full of freedom, independent, but sexually objectified and individualist.